2008
DOI: 10.1097/md.0b013e318181e6af
|View full text |Cite
|
Sign up to set email alerts
|

Primary Sjögren Syndrome in Spain

Abstract: We conducted the current study to characterize the clinical presentation of primary Sjögren syndrome (SS) in a large cohort of Spanish patients and to determine whether epidemiologic, clinical, and analytical features modulate disease expression. Patients were from the GEMESS Study group, which was formed in 2005 and included 12 Spanish reference centers. By March 2007, the database included 1010 consecutive patients, recruited since 1994, both incident and prevalent cases. The cohort included 937 women and 73… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
133
4
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 481 publications
(158 citation statements)
references
References 37 publications
(63 reference statements)
8
133
4
2
Order By: Relevance
“…Data on the prevalence of renal disease in pSS comes from two sources; retrospective studies looking for overt renal dysfunction, mainly defects in excretory renal function and proteinuria [5, 12, 13], and smaller prospective series in which tubular defects were explicitly screened for [3, 14–16]. While the retrospective studies found a rate of renal involvement in pSS of 4.3–6.5 % [5, 12, 13], the prospective studies observed a much higher rate of 28–42 % [3, 15].…”
Section: Discussionmentioning
confidence: 99%
“…Data on the prevalence of renal disease in pSS comes from two sources; retrospective studies looking for overt renal dysfunction, mainly defects in excretory renal function and proteinuria [5, 12, 13], and smaller prospective series in which tubular defects were explicitly screened for [3, 14–16]. While the retrospective studies found a rate of renal involvement in pSS of 4.3–6.5 % [5, 12, 13], the prospective studies observed a much higher rate of 28–42 % [3, 15].…”
Section: Discussionmentioning
confidence: 99%
“…These criteria enable one to make a diagnosis of SS in a patient with suggestive clinical presentation and objective evidence such as histopathology and antibodies, even if patient does not volunteer sicca symptoms. A large number of studies on SS have come out in published literature mainly from the European populations, which primarily serve as the source of guiding principles for clinical diagnosis [5-8]. With the exception of a Chinese study, there is a paucity of data on clinical characteristics and epidemiological information from populations other than those of European ancestry [9].…”
Section: Introductionmentioning
confidence: 99%
“…SS has also been linked with pneumatosis cystoides intestinalis [11], colon cancer [12, 13], protein-losing gastroenteropathy [14], and intestinal pseudoobstruction [15]. Involvement of internal organs is more likely if the vasculitis is associated with cryoglobulins [16]. …”
Section: Discussionmentioning
confidence: 99%